Advancing Concrete Pavement Rehabilitation and Strategic Management Through Nondestructive Testing at Toll Stations - Konstantinos Gkyrtis; Christina Plati; Andreas Loizos (Applied Sciences)
In contrast to maintaining asphalt pavements, maintaining healthy and functional concrete pavements is a much greater challenge due to the especially brittle nature of concrete, which may require a more complex rehabilitation plan. Thanks to nondestructive testing, noninvasive on-site inspections can be carried out to assess a pavement’s condition, with the falling weight deflectometer (FWD) being the most representative example. In this study, five toll stations with concrete pavements in operation, for which no long-term monitoring protocols existed yet, were evaluated mainly with deflectometric tests using the FWD. The objective of the study was to propose a methodological framework to support responsible decision-makers in the strategic management of concrete pavements at toll stations. To meet this aim, a test campaign was organized to evaluate the pavement condition of individual slabs or lanes, assess the durability of the slabs, and determine the efficiency of load transfer across joints and cracks. As a key finding, pavement slab deflections were found to exhibit a considerable range; in particular, a range of 50–1450 μm for the maximum deflection of the FWD was observed. This finding stimulated a distribution fitting analysis to estimate characteristic values and thresholds for common deflection indicators that were validated on the basis of pavement design input data. Finally, the study proceeded with the development of a conceptual approach proposing evaluation criteria for individual slab assessment and the condition mapping of in-service concrete pavements.